2016
DOI: 10.1007/s13353-016-0363-4
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for earliness and yield-forming traits in the Lubuski × CamB barley RIL population under various water regimes

Abstract: Drought has become more frequent in Central Europe causing large losses in cereal yields, especially of spring crops. The development of new varieties with increased tolerance to drought is a key tool for improvement of agricultural productivity. Material for the study consisted of 100 barley recombinant inbred lines (RILs) (LCam) derived from the cross between Syrian and European parents. The RILs and parental genotypes were examined in greenhouse experiments under well-watered and water-deficit conditions. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 99 publications
(138 reference statements)
3
52
0
Order By: Relevance
“…() and Ogrodowicz et al. () in the RIL populations, only five QTLs exhibiting the same additive effect as that in the mapping study were found in both Experiment I and Experiment II. This was not unexpected, as the fine positioning and estimated QTL effects are known to depend on the population.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…() and Ogrodowicz et al. () in the RIL populations, only five QTLs exhibiting the same additive effect as that in the mapping study were found in both Experiment I and Experiment II. This was not unexpected, as the fine positioning and estimated QTL effects are known to depend on the population.…”
Section: Discussionsupporting
confidence: 69%
“…() and Ogrodowicz et al. (), 74 were selected for the traits that could be associated with the traits observed in Experiment I or Experiment II (Supporting information Table ; 1,000‐grain weight—TGW; grain weight per square metre, grain weight per plant—GWP, GY; length of the main stem—LMS, PH; number of productive tillers per plant—NPT). Alleles increasing values of the traits (positive alleles) and the markers closest to the QTLs were defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations